Enhancing resilience in sexual harassment victims using narrative exposure therapy: a single case research - Hunafa, Saifa; Sugara, Gian Sugiana; Muhajirin, Muhammad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Victims of sexual harassment often experience deep trauma, such as feelings of shame, fear, anger, and loss of self-worth. Intervention using Narrative Exposure Therapy (NET) aims to enhance resilience in victims of sexual harassment and reduce the trauma symptoms they endure. The subject chosen for this study is a female college student who has been a victim of sexual harassment and met the study criteria. This research was designed using a single-case study approach with an A-B-A model. Using the Adolescent Resilience Scale, the participant showed a reduction of (d = 5.7); and using the PTSD Checklist-5 (PCL-5), the participant showed a reduction of (d = 4.87). These results indicate that resilience scores increased, and PTSD scores decreased from the baseline phase (A1) to the follow-up baseline phase (A2) using NET. The findings demonstrate that the NET approach is highly beneficial and necessary for counselors and school guidance teachers to help victims reduce PTSD symptoms and enhance resilience.